Pengaruh Kualitas Pelayanan, Kualitas Produk, Harga dan Lokasi Terhadap Keputusan Pembelian di Family Mart Embong Malang Surabaya - Gandawidjaya, Valentine; Pahar, Bruno Hami; Sukianto, Gunawan (Universitas Katolik Darma Cendika, 2025)
Family Mart is a company engaged in the retail sector. Retail is an easy access that is created so that consumers can easily shop, the purpose of conducting research on Family Mart Embong Malang Surabaya is to find out if there is an influence on Product Quality, Service Quality, Price and Location on Purchase Decisions. The type of research used by researchers is quantitative. The sample in this study is 100 respondents who have made a purchase at Family Mart Embong Malang Surabaya 1 time. The sampling technique in this study uses the purposive sampling method and the type of data used is primary data. The data collection method uses a questionnaire. The research data was processed using SPSS version 26. The results of the data analysis show that all variable statement items are declared valid with calculation > rtable. The results of the reliability test showed that all variables were declared reliable because Cronbach's Alpha value > 0.60. The results of the normality test with the P-P Plot showed that the data used was normally distributed. As for the heterokedastias test, it did not show any heterokedasticity symptoms in the regression model because there was no clear pattern shape and there was a distribution of points above and below the number 0 on the Y axis. Multiple linear equations Y = 0.161 + 0.219 X1 +0.203 X2 + 0.236 X3 + 0.186 X4. The determination coefficient in this study shows that the Adjusted R Square value is 0.787 or equivalent to 78.7% so that it can be interpreted that the independent variable contributes to the dependent variable. The results of the t-test in this study show that service quality (X1), product quality (X2), price (X3) and location (X4) have a significant effect on purchase decisions.